Intraoperative Rerupture and Surgical Clipping of a Small Superiorly Projecting Anterior Communicating Artery Aneurysm: 2‐Dimensional Operative Video. Issue 3 (September 2020) - Hendricks, Benjamin K.; Spetzler, Robert F.
Abstract : N/A: Anterior communicating artery (ACoA) aneurysms are prone to rupture even at smaller sizes. The surgical management of ACoA aneurysms is highly dependent on the spatial orientation of the saccular projection, categorized as inferior, superior, anterior, or posterior. Superior projecting aneurysms constitute approximately one‐third of all aneurysms involving the ACoA. These aneurysms commonly project within the interhemispheric fissure; however, if the aneurysm is not high‐riding, it can often be approached via a transsylvian trajectory. The patient presented after subarachnoid hemorrhage with a 3‐mm superiorly projecting ACoA aneurysm. The lesion was approached via a right modified orbitozygomatic craniotomy with a transsylvian trajectory. The aneurysm reruptured after minimal manipulation of the dome. Mitigation of the intraoperative rupture was achieved through temporary clip application to bilateral A1 vessels. Bipolar coagulation and placement of 2 permanent clips facilitated final aneurysm occlusion. Postoperative imaging demonstrated patent bilateral A2 flow and no residual aneurysm filling. The patient gave informed consent for surgery and video recording. Institutional review board approval was deemed unnecessary. Used with permission from Barrow Neurological Institute, Phoenix, Arizona.